Radical Social Work. Issue 2 (4th May 2017) - Cardenas, Iris
Abstract: Social workers often concentrate efforts in alleviating individual-level problems but neglect systematic factors that contribute to those problems. This article encourages professionals in the field to actively analyze the implementation of policies and its impact in populations by engaging in what the author calls radical vision. This article further discusses the contribution of localism and de facto segregation to the perpetuation of poverty and inequality.